OWN CAPITAL, LOAN CAPITAL, AND EARNINGS Of BUSINESS RETURNS WITH A CAUSALITY APPROACH - Reza Nofita; Muhammad Rivandi (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2023)
The welfare of cooperative members is reflected in the remaining results of operations which continue to increase. This study aims to determine the effect of own capital and loan capital on the remaining results of operations at the Padang City savings and loan cooperative for the 2019-2021 period. The population in this study is the Padang City Savings and Loans Cooperative for the period 2019-2021. The sample of savings and loan cooperatives in the study totaled 15 savings and loan cooperatives in the city of Padang with an observation period of 3 years, namely 2019-2021. The sampling method used purposive sampling technique. The analytical method uses regression model panel data. The results showed that, own capital has a negative and significant effect on the remaining results of operations and loan capital has a positive and significant effect on the remaining results of operations. Keywords: Loan Capital, Own Capital, Earnings Of Business Returns.